Penggunaan Komunikasi Bluetooth Pada Smartphone Android Untuk Pengiriman Data Pada Jam Digital Berbasis Arduino - Sarifudin, Sarifudin; Manshur, Manshur; Tirtana, Angga (P3M Politeknik Negeri Banjarmasin, 2017)
The schedule of prayer is very important akan ada.Masa Today many in the mosque as well as in homes that usually have a calendar and the viewer time of eternal prayer, but it looks so small that it can not be seen from a great distance. This prayer timepiece uses a display display dot matrix P4, displaying the date, digital clock as well as the 5th time of the prayer. So that prayer times can be changed in real time according to time and day changes, and can be seen from a great distance and can be used to maximize the time available. This research produces a digital clock time system that uses dot-matrix as display, RTC as real time clock, bluetooth as sender of data from smart mobile device android, and buzzer as alarm. So that the system formed the digital clock time of this prayer. Based on design, implementation and testing, the arduino-based digital time-shaped design tool can be used for digital clocks and bookmarks and prayer time reminders.